Development of a CFD model and procedure for flows through in-stream structures. (3rd July 2022) - Lai, Yong G.; Smith, David L.; Bandrowski, David J.; Xu, Yuncheng; Woodley, Christa M.; Schnell, Kaitlin
Abstract : Large wood (LW) has been widely used in river restoration projects due to its ecological benefit. 3D modeling has rarely been conducted. In this study, a 3D modeling procedure is proposed and a new 3D model is developed. The model incorporates advanced CFD techniques and is easy to apply. An engineered log jam (ELJ) is constructed and an experiment is conducted. The data are used to demonstrate the procedure and validate the CFD model. A comparison of the predicted and measured velocity shows that agreement is good with the Nash-Sutcliffe coefficient about 0.4 and index of agreement about 0.85. The model is further applied to a curved channel with ELJ on the outer bank, demonstrating the use of the 3D model to guide the proper representation of ELJs in a 2D model. The 3D model may be used to reveal complex flow patterns generated by LW for ecological benefit analysis.